2015
DOI: 10.1115/1.4030437
|View full text |Cite
|
Sign up to set email alerts
|

A Random Field Approach to Reliability Analysis With Random and Interval Variables

Abstract: Interval variables are commonly encountered in design, especially in the early design stages when data are limited. Thus, reliability analysis (RA) should deal with both interval and random variables and then predict the lower and upper bounds of reliability. The analysis is computationally intensive, because the global extreme values of a limit-state function with respect to interval variables must be obtained during the RA. In this work, a random field approach is proposed to reduce the computational cost wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Since the development of the first adaptive surrogate modelingbased reliability analysis method in 2008 by Bichon et al [14], adaptive surrogate modeling has gained much attention in recent year in the reliability analysis field due to its promising potential in overcoming the drawbacks of traditional reliability analysis methods, such as the first-order reliability method [39] and second-order reliability method [40]. It has shown that the adaptive surrogate modeling-based reliability analysis method can dramatically improve the efficiency of reliability analysis while maintaining satisfactory accuracy [41].…”
Section: Collision-avoidance Reliability Analysis Based Onmentioning
confidence: 99%
“…Since the development of the first adaptive surrogate modelingbased reliability analysis method in 2008 by Bichon et al [14], adaptive surrogate modeling has gained much attention in recent year in the reliability analysis field due to its promising potential in overcoming the drawbacks of traditional reliability analysis methods, such as the first-order reliability method [39] and second-order reliability method [40]. It has shown that the adaptive surrogate modeling-based reliability analysis method can dramatically improve the efficiency of reliability analysis while maintaining satisfactory accuracy [41].…”
Section: Collision-avoidance Reliability Analysis Based Onmentioning
confidence: 99%
“…This is similar to random responses at different locations of a random field. Modeling system responses as a random field for system reliability analysis has been investigated in Hu and Du (2015) and Hu and Mahadevan (2015 b ) based on FORM. In this paper, this concept is further extended for surrogate modeling-based system reliability analysis by using the SVD (Chatterjee, 2000) or proper orthogonal decomposition (Palmer et al, 2012).…”
Section: Proposed Efficient Kriging Surrogate Modeling Approach (Eksa)mentioning
confidence: 99%
“…Furthermore, hybrid reliability models, involving both probabilistic and nonprobabilistic uncertainties, have attracted growing attention over the last decade (see, e.g., Refs. [21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%